Endoplasmic reticulum stress mediates inflammatory response triggered by ultra-small superparamagnetic iron oxide nanoparticles in hepatocytes. Issue 10 (26th November 2018) - He, Chengyong; Jiang, Shengwei; Yao, Huan; Zhang, Liyin; Yang, Chuanli; Zhan, Denglin; Lin, Gan; Zeng, Yun; Xia, Yankai; Lin, Zhongning; Liu, Gang; Lin, Yuchun
Abstract: Ultra-small superparamagnetic iron oxide nanoparticles (USPIO-NPs) are widely used as clinical magnetic resonance imaging contrast agents for hepatic diseases diagnosis. USPIO-NPs often damage the hepatocytes and affect the function of liver but its mechanism of action remains unclear. In the present study, USPIO-NPs caused higher cytotoxicity and lactate dehydrogenase (LDH) leakage in hepatic L02 cells than SPIO-NPs. Subsequently, USPIO-NPs affected more genes' expression than SPIO-NPs analyzed through microarray and bioinformatics analysis. The affected genes were involved in several biological processes, including calcium ion homeostasis, inflammatory response-related leukocyte chemotaxis, and migration. In addition, the level of endoplasmic reticulum (ER) calcium ion was increased by USPIO-NPs. USPIO-NPs also upregulated the genes related to acute-phase inflammation, including IL1B, IL6, IL18, TNFSF12, TNFRSF12, SAA1, SAA2, JAK1, STAT5B, and CXCL14 . Furthermore, interleukin-6 (IL-6) secretion was elevated by USPIO-NPs as detected using ELISA. On the other hand, USPIO-NPs changed the morphology of ER and triggered the ER stress and unfolded protein response PERK/ATF4 pathway. Furthermore, blocking ER stress with inhibitor or ATF4 small interfering RNA counteracted IL-6-related acute-phase inflammation and cytotoxicity caused by USPIO-NPs. Taken together, we found that the USPIO-NPs could trigger stronger IL-6-related acute-phase inflammation than SPIO-NPs in hepatocytes. We demonstrated, for the first time, that IL-6-related acute-phase inflammation caused by NPs was regulated by PERK/ATF4 signaling. The PERK/ATF4 pathway explored in this study could be a candidate for diagnostic and therapeutic target against NPs-induced liver injury and cytotoxicity, which would be helpful for USPIO-NPs medical application.